Kegiatan Penyuluhan Hukum Keluarga Islam terhadap Peningkatan Kesadaran Ibu Rumah Tangga tentang Hak dan Kewajiban dalam Rumah Tangga - Saidah Fiddaroini Harun (Jurnal Pengabdian Masyarakat, 2026)
This community service activity was motivated by the low awareness of housewives regarding their rights and obligations within the household based on Islamic family law in Rungkut Menanggal Village, Surabaya. The objective of this activity was to increase understanding and legal awareness through participatory education and counseling. The method used was the Asset Based Community Development (ABCD) approach with five main stages: discovery, dream, design, definition, and implementation/destiny, as well as data collection techniques through interviews. The results of the activity showed an increase in participants’ understanding of the concept of rights and obligations within the household, which was characterized by active participation in discussions and the ability of participants to connect the material with everyday experiences. In addition, this activity also encouraged the formation of collective awareness in building harmonious families based on Islamic legal values. The implications of this activity indicate that community empowerment-based legal counseling can be an effective strategy in improving the quality of family life and strengthening community social resilience in a sustainable manner.